Comparison of immediate colposcopy, repeat conventional cytology and high‐risk human papillomavirus testing for the clinical management of atypical squamous cells of undetermined significance cytology in routine health services of Medellin, Colombia: The ASCUS‐COL trial. Issue 6 (24th October 2020) - Baena, Armando; Agudelo, Maria C.; Lopez, Carolina; Ramírez, Arianis Tatiana; Castañeda, Kelly Melisa; Bedoya, Astrid M.; Riveros, Marcela; Posada, Guadalupe; Borrero, Mauricio; Buitrago, Carlos A.; Suescun, David; Gomez, Luis J.; et al.
Abstract: In the context of opportunistic cervical cancer screening settings of low‐and‐middle‐income countries, little is known about the benefits of high‐risk human papillomavirus (hrHPV) testing on high‐grade cervical abnormality detection among women with atypical squamous cells of undetermined significance (ASC‐US) cytology in routine clinical practice. We compared the effectiveness of immediate colposcopy (IC), conventional cytology at 6 and 12 months (colposcopy if ≥ASC‐US) (RC) and hrHPV testing (colposcopy if hrHPV‐positive) (HPV) to detect cervical intraepithelial neoplasia grade 2 or more severe diagnoses (CIN2+) among women aged 20 to 69 years with ASC‐US in routine care. Participants (n = 2661) were evenly randomized into three arms (n = 882 IC, n = 890 RC, n = 889 HPV) to receive services by routine healthcare providers and invited to an exit visit 24 months after recruitment. Histopathology was blindly reviewed by a quality‐control external panel (QC). The primary endpoint was the first QC‐diagnosed CIN2+ or CIN3+ detected during three periods: enrolment (≤6 months for IC and HPV, ≤12 months for RC), follow‐up (between enrolment and exit visit) and exit visit. The trial is completed. Colposcopy was done on 88%, 42% and 52% of participants in IC, RC and HPV. Overall, 212 CIN2+ and 52 CIN3+ cases were diagnosed. No differences were observed for CIN2+ detection ( P = .821). However, compared to IC, only HPV significantly reduced CIN3+ cases that providers were unable to detect during the 2‐year routine follow‐up (relative proportion 0.35, 95% CI 0.09‐0.87). In this context, hrHPV testing was the most effective and efficient management strategy for women with ASC‐US cytology. What's new?: Guidelines for high‐risk human papillomavirus (hrHPV) testing in cervical cancer screening were introduced in Colombia in 2014 but have yet to be adopted in clinical practice. Moreover, follow‐up for screen‐positive women, including those with atypical squamous cells of undetermined significance (ASC‐US) cytology is limited. Here, hrHPV testing for follow‐up of women with ASC‐US cytology was compared with two approaches currently available in Colombia, immediate colposcopy and repeat cytology at two‐year routine follow‐up. Compared to immediate colposcopy, hrHPV testing reduced the burden of high‐grade cervical abnormalities by 65 percent and colposcopy referral by 41 percent.